The Influence of Digital Marketing and Social Media Engagement on Repurchase Intention with Customer Trust as a Mediating Variable in Fast Food - Hidayat, Yudha Rahmat; Komaryatin, Nurul (Manunggal Halim Jaya, 2026)
This study aims to examine the impact of Digital Marketing and Social Media Engagement on Repurchase Intention, with Customer Trust acting as a mediating variable among Mie Gacoan Jepara consumers. The background of the research is based on the growing trend of noodle consumption in Indonesia and high social media activity, which creates opportunities for culinary businesses to strengthen customer loyalty. A quantitative survey was conducted with 128 respondents who had purchased Mie Gacoan products at least twice. Data were analyzed using Partial Least Squares (PLS) with SmartPLS 4.0 software. The results show that Digital Marketing significantly and positively affects Repurchase Intention (β = 0.238; p = 0.016) and Customer Trust (β = 0.406; p = 0.000). Similarly, Social Media Engagement significantly influences both Repurchase Intention (β = 0.309; p = 0.001) and Customer Trust (β = 0.324; p = 0.007). Additionally, Customer Trust has a significant positive impact on Repurchase Intention (β = 0.314; p = 0.000). The analysis of indirect effects indicates that Customer Trust partially mediates the effects of Digital Marketing (t = 2.369; p = 0.018) and Social Media Engagement (t = 1.969; p= 0.049) on Repurchase Intention. In conclusion, Customer Trust plays a vital mediating role in strengthening the relationship between digital marketing strategies and repurchase intention. Therefore, Mie Gacoan should enhance its digital marketing and social media engagement strategies to maintain customer trust and promote repeat purchases.